REINTERPRETASI PENDAPA PADA DESAIN INTERIOR â€œTHIRD SPACEâ€ SEBAGAI FASILITAS KOMUNITAS MENUJU SOLO KOTA KREATIF - Hastuti, Dhian Lestari; Santosa, Cahyono Budi (Acintya, 2017)
Surakarta is one of initiators of Indonesia Creative Cities Network (ICCN), which takes importantrole in the establishment of Creative Cities in Indonesia. It required synergy among penta helix academicians, businessmen/ladies, government, people, and medias to produce creative ecosystem. WhileSurakarta community is the center of the implementation and program implementation and creativeeconomic development program within the pattern of interaction, connection and collaboration offive (5) elements mentioned above. In order to create the pattern, it requires informal and formalspace to facilitate creative activity for community members. In urban community this space namedThird Space which is a new space typology after a home and work place. In Javanese community thefunction of this space provided by pendapa. Pendapa has been long time to function as a place forsocial interaction between the host and its neighborhood. This article is a result of artistic researchwhich shows reinterpretation of immaterial value of pendapa into architecture and Third Space interior design. Design method based on user need and three various research methodologies, namelyscenario based survey, co-creation session and focused interview. Philosophy, socio-culture, function and ergonomic approaches are used as a base to redesign pendapa. It achieves ‘’meeting tree’’ orkayon, a two (2) floors building with Indisch style, Scandinavian interior design. The process andThird Space design produce synergy embodiment between academician and community to supportSolo, A Creative City program.Keywords: Creative City, penta helix synergy, community, reinterpretation of pendapa, kayon, Scandinavian design.